An Analysis of the Effectiveness of Farm Road Development on Productivity and Farmer Welfare in Lamongan Regency - Ida Suryawati (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2026)
The development of agricultural infrastructure, particularly farm roads, constitutes a strategic policy intervention designed to enhance food security, agricultural productivity, and the welfare of farmers in Lamongan Regency. This study aims to critically evaluate the effectiveness of farm road construction on optimizing crop yields and improving the socio-economic resilience of rural agrarian communities. Employing a comprehensive mixed-methods approach, the research integrates quantitative and qualitative data acquired through in-depth interviews, direct field observations, and the analysis of institutional documents. The findings reveal that farm road development significantly improves spatial accessibility, substantially reduces logistical transportation costs, and curtails post-harvest losses. These improvements cumulatively elevate agricultural productivity and drive a consistent upward trajectory in the Farmers' Terms of Trade (NTP). Furthermore, the infrastructure democratizes market access by dismantling oligopsonistic practices, thereby amplifying the bargaining power of primary producers. However, the long-term efficacy of this development is impeded by persistent structural constraints, including the absence of systematic post-construction maintenance, uneven infrastructural quality across the region, and the escalating threat of productive land capitalization. The study concludes that while farm roads are highly effective in augmenting immediate agrarian welfare, sustaining these socio-economic benefits necessitates the rigorous integration of Environmental, Social, and Governance (ESG) principles, stringent spatial planning, and robust grassroots institutional empowerment.